2015
DOI: 10.1002/ejic.201500313
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Iron Hydrides by Selective C–F/C–H Bond Activation in Fluoroarylimines and Their Applications in Catalytic Reduction Reactions

Abstract: The reactions of Fe(PMe3)4 with different 2,6‐diflurophenylarylimines 1–5 were explored. Fluoroarylimines 1–3, the aryl rings of which are substituted with electron‐withdrawing groups, reacted with Fe(PMe3)4 to afford the C–H activation products 6–8. However, if the aryl rings of the fluoroarylimines were substituted with electron‐donating groups, the iron hydrides 9 and 10 were obtained from the reactions of the fluoroarylimines with Fe(PMe3)4 through C–F bond activation. In a further study, silanes, especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 122 publications
1
8
0
Order By: Relevance
“…Obviously, complex 6 is a good catalyst for the selective reduction of CO bonds of α,β-unsaturated aldehydes and ketones. This selectivity is similar to that of our earlier reported system . Regrettably, the yields (Table ) are not as good as those of Beller with fluoro­(tris­(2-(diphenylphosphino)­phenyl)­phosphino)iron tetrafluoroborate as catalyst …”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Obviously, complex 6 is a good catalyst for the selective reduction of CO bonds of α,β-unsaturated aldehydes and ketones. This selectivity is similar to that of our earlier reported system . Regrettably, the yields (Table ) are not as good as those of Beller with fluoro­(tris­(2-(diphenylphosphino)­phenyl)­phosphino)iron tetrafluoroborate as catalyst …”
Section: Resultssupporting
confidence: 88%
“…The selective hydrogenation of alkyne to trans -alkene and selective reduction of the carbonyl group of α,β-unsaturated ketones were realized with iron hydries by Bianchini’s group. , Several reports on hydrosilylation with iron hydrides as catalysts were published . Recently, we have found that several pincer iron­(II) hydrides and bidentate iron­(II) hydrides can be used as catalysts in the reduction of carbonyl groups with triethyloxysilane as the reduction reagent. As a continuation of our study in this direction, complexes 1 – 4 and 6 were used as catalysts to explore their performance in the hydrosilylation of carbonyl compounds.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“… Some notable recent examples of catalytic hydrosilylation of imines using late transition metals include the (μ-silane)­diruthenium complex I by Kira, silylene-bridged iridium dimer complex II by Brookhart and also the bowl-shaped phosphine complex of rhodium III by Tsuji (Chart ). Consequently, an inexpensive and environmentally benign transition-metal surrogate, replacing scarce, toxic, and expensive transition metals, is a pressing need . In this direction, the use of normal N-heterocyclic carbenes ( n NHCs) has shown promise in designing base-metal catalysts for imine reduction .…”
mentioning
confidence: 99%
“…Aer the addition of silane (at 27 min), the concentration of the benzaldehyde decreased signicantly and the silicon ether increased remarkably. Combined with our previous work, 28,29 we believe that this catalytic reaction is the result of synergy of benzaldehyde, complex 1 and silane. More work is needed to explain the details of the mechanism.…”
Section: Rcho þ ðEtoþmentioning
confidence: 83%